2021
DOI: 10.1016/j.scitotenv.2020.141855
|View full text |Cite
|
Sign up to set email alerts
|

Multi-city comparative PM2.5 source apportionment for fifteen sites in Europe: The ICARUS project

Abstract: Source apportionment was applied for 15 sites from 5 cities in Europe. • PMF harmonized application was based on common sampling and analysis protocol. • Traffic and biomass burning were the major control-demanding sources. • The homogeneity of PM 2.5 source chemical profiles was examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 54 publications
(61 reference statements)
1
8
0
Order By: Relevance
“…Combining elemental and ionic composition (airborne concentrations are reported in Table S2 and Table S4), OC and BC content, PMF analysis was further performed and confirmed traffic as the main PM pollution source in Ljubljana, Slovenia, contributing with 30 % to the investigated PM2.5 mass. Similar has been observed by Saraga et al (2021). The other factors, which together with traffic accounted for roughly 96 % of the analysed PM, are: secondary inorganic aerosols (nitrate (15 %) and sulphate (18 %)), biomass burning (14 %), mineral dust (12 %), and marine- Nitrate (factor 1) and sulphate (factor 4), as indicators of inorganic secondary atmospheric aerosols that may have travelled long distances, are characteristic of different seasons, i.e.…”
Section: Characterization and Source Apportionment Of Atmospheric Aer...supporting
confidence: 90%
“…Combining elemental and ionic composition (airborne concentrations are reported in Table S2 and Table S4), OC and BC content, PMF analysis was further performed and confirmed traffic as the main PM pollution source in Ljubljana, Slovenia, contributing with 30 % to the investigated PM2.5 mass. Similar has been observed by Saraga et al (2021). The other factors, which together with traffic accounted for roughly 96 % of the analysed PM, are: secondary inorganic aerosols (nitrate (15 %) and sulphate (18 %)), biomass burning (14 %), mineral dust (12 %), and marine- Nitrate (factor 1) and sulphate (factor 4), as indicators of inorganic secondary atmospheric aerosols that may have travelled long distances, are characteristic of different seasons, i.e.…”
Section: Characterization and Source Apportionment Of Atmospheric Aer...supporting
confidence: 90%
“…In this study, 24-h air samples of fine particles (i.e. <2.5 μm, PM 2.5 sampling head) were collected within the ICARUS air sampling campaign ( Saraga et al, 2021 ) in winter and summer 2017 at a traffic (T), and an urban background (UB) sites in Brno (N = 60 for both T and UB) and Ljubljana (N = 56 and 60 for T and UB), as well as at a rural (R) site in the Czech Republic (N = 16, Table S1 in the Supplementary information). Both traffic sites were located close to the city center, few meters away in Brno and about 100 m away in Ljubljana from a busy road with frequent congestion ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the targeted analytes, PAHs, PM 2.5 , toxic metals (e.g. Cu, Zn), elemental (black) and organic carbon, anions and cations were also determined in these samples (see Saraga et al, 2021 , for more details). Moreover, the concentrations of additional air pollutants (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Two seasons of synchronous sampling across 15 sites in Europe (ICARUS EU2020 project) [77] indicated the contributions to PM 2.5 concentration as follows: high traffic sites had the highest contribution of traffic exhausts (23.3%), urban background sites had highest traffic non-exhaust (13.5%) and biomass burning (30%), and rural sites had the highest contribution of oil combustion (18.7%) and soil dust (16%). Overall, the study results showed that, while fuel oil combustion, traffic non-exhausts, and soil dust profiles are varied between sites, biomass burning, sea salt, and traffic exhaust were characterized as relatively homogenous among the sites.…”
Section: Waste Incinerationmentioning
confidence: 99%